Genetic structure and diversity of Mycoplasma hyopneumoniae based on a MLVA typing scheme - Pablo Tamiozzo; Virginia García; Raúl E. González-Ittig; Raúl E. González-Ittig; Maria Pieters; Maria Pieters; Maria Pieters (Frontiers in Veterinary Science)
BackgroundSeveral epidemiological studies have been carried out using Multiple-Locus Variable-number tandem repeat Analysis (MLVA) for M. hyopneumoniae typing. However, a global perspective on the implications of the genetic diversity of this pathogen is lacking.ObjectiveThis study aimed to determine and to analyze the genetic structure of M. hyopneumoniae based on the p97R1-p146R3 MLVA typing scheme and to characterize, analyze and compare MLVA types among countries where the information was publicly available.MethodsA set of 797 publicly available data of M. hyopneumoniaep97R1-p146R3 MLVA genetic types from six different countries were analyzed using Genalex 6.41 software to characterize loci polymorphism and using Structure 2.3.4 software in order to identify the genetic structure.ResultsA total of 185 MLVA types were identified among the analyzed data. For the p97R1 and p146R3 loci, most of the molecular variation in M. hyopneumoniae populations was identified within countries. Three genetic clusters and their recombinations were identified globally.ConclusionM. hyopneumoniae is a genetically diverse pathogen with limited clonality and three well-defined clusters and their combinations were identified in this investigation. The greatest genetic variation of M. hyopneumoniae was observed within countries.